Friends of the Earth International: agonistic politics, modus vivendi and political change - Doherty, B.; Doyle, Timothy (Routledge, 2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group Following criticism from some of its national member organisations that it marginalised, Southern agendas, Friends of the Earth International (FoEI), engaged in heated debates in the 2000s that aimed to address its internal political differences. FoEI defined its positions on democracy, capitalism and social transformation, reorienting itself more towards the global South. The centrality to this process of debate about broad political ideas is unusual; well established and mature organisations do not usually change identities fundamentally. In practice, FoEI did not resolve its differences, but came to a political settlement which made those differences manageable. To interpret the changes in FoEI, the concept of agonistic politics developed by Chantal Mouffe and the idea of a modus vivendi associated with so called realist (liberal) critics of ‘moralistic liberalism’ are employed. A full account of the process nevertheless requires acknowledgement of the positive effect of solidarity as enabling changes in collective identity.